2010
DOI: 10.1088/2041-8205/713/2/l187
|View full text |Cite
|
Sign up to set email alerts
|

DISCOVERY OF A RED GIANT WITH SOLAR-LIKE OSCILLATIONS IN AN ECLIPSING BINARY SYSTEM FROM KEPLER SPACE-BASED PHOTOMETRY

Abstract: Oscillating stars in binary systems are among the most interesting stellar laboratories, as these can provide information on the stellar parameters and stellar internal structures. Here we present a red giant with solar-like oscillations in an eclipsing binary observed with the NASA Kepler satellite. We compute stellar parameters of the red giant from spectra and the asteroseismic mass and radius from the oscillations. Although only one eclipse has been observed so far, we can already determine that the second… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

6
3

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 22 publications
4
71
0
1
Order By: Relevance
“…Finally, we note that KIC 8410637, an eclipsing binary with a 408 d period (Hekker et al 2010;Frandsen et al 2013) has a period and a high eccentricity (e ∼ 0.7), compatible with the other red giant heartbeat stars (Figs. 18 & 19) but no heartbeat events are visible.…”
Section: Comparison To Other Known Red Giant Stars In Eccentric Binarsupporting
confidence: 66%
See 1 more Smart Citation
“…Finally, we note that KIC 8410637, an eclipsing binary with a 408 d period (Hekker et al 2010;Frandsen et al 2013) has a period and a high eccentricity (e ∼ 0.7), compatible with the other red giant heartbeat stars (Figs. 18 & 19) but no heartbeat events are visible.…”
Section: Comparison To Other Known Red Giant Stars In Eccentric Binarsupporting
confidence: 66%
“…KIC 5006817 is marked with a cross. The eclipsing red giant KIC 8410637 (Hekker et al 2010;Frandsen et al 2013) is shown as a triangle. The stars found in the LMC (Nicholls & Wood 2012) are shown as squares.…”
Section: Impact Of Stellar Evolution On Eccentric Binary Systemsmentioning
confidence: 99%
“…The best way to measure stellar masses is to use binary systems for which the orbital motion can be observed either by spectroscopy or by imagery. Many eclipsing binaries having an oscillating red giant component have been discovered by Hekker et al (2010) and Gaulme et al (2013). These eclipsing binaries have a rather short orbital period that allows an efficient measurement of radial velocity, thereby providing an orbital solution of the system (Beck et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, efforts were made to exploit the combination of binarity and asteroseismology, in particular with data from the NASA Kepler mission. Hekker et al (2010) and Frandsen et al (2013) reported the identification of the eclipsing binary system KIC 8410637, composed of an F star and a red giant that exhibit solar-like oscillations. Metcalfe et al (2012a) performed the seismic analysis of the binary system 16 Cyg A and B, where eigenmodes of oscillations were identified for both solar-type stars.…”
Section: Introductionmentioning
confidence: 99%